APLIKASI PENGOLAHAN DATA PRESENSI PEGAWAI BERBASIS WEB PADA BADAN KEPEGAWAIAN DAERAH PEMERINTAH KOTA JAMBI - Pariyadi - (JURNAL AKADEMIKA)
Presence application of data processing applications and utilizing Internet Of Things (IOT) in the local civil environment jambi city government is expected to improve the culture of employee discipline, integrity and responsibility. Presence process using biometric engine performed by every employee in every office SKPD / UPT then the data will be directly sent to the server. Furthermore, the application will process the data so that it can be separated based on personal data and classified based on data per SKPD / UPT. After the application of data processing applications presensi increased labor discipline of employees and employee presence information can be easily and orderly prepared by staffing agencies Jambi City area.